2013
DOI: 10.1673/031.013.11201
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral, Immunomodulatory, and Free Radical Scavenging Activities of a Protein-Enriched Fraction from the Larvae of the Housefly,Musca domestica

Abstract: In our previous study, protein-enriched fraction (PEF) that was isolated from the larvae of the housefly, Musca domestica L. (Diptera: Muscidae), showed excellent hepatoprotective activity as well as the potential for clinical application in therapy for liver diseases. In this study, antiviral, immunomodulatory, and free radical scavenging activities of PEF were evaluated. The antiviral results demonstrated that PEF inhibited the infection of avian influenza virus H9N2 and had a virucidal effect against the mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 32 publications
(36 reference statements)
0
12
0
Order By: Relevance
“…However, the housefly itself stays uninfected, mainly because of its powerful congenital immune system. [10][11][12] Reportedly, house flies can produce attacin, cecropin, defensin, diptericin, and other AMP molecules to resist the invasion of pathogens. 13 These biologically active proteins and peptides are considered potential alternatives to the conventional antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…However, the housefly itself stays uninfected, mainly because of its powerful congenital immune system. [10][11][12] Reportedly, house flies can produce attacin, cecropin, defensin, diptericin, and other AMP molecules to resist the invasion of pathogens. 13 These biologically active proteins and peptides are considered potential alternatives to the conventional antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, antimicrobial peptides such as cecropin, defensin attacin, and MDpep9 have been paid an extensive attention [ 6 8 ]. Antimicrobial peptides of M. domestica larvae have been shown to possess the antioxidant [ 9 ], antitumor [ 10 , 11 ], anti-inflammatory [ 12 ], anti-atherosclerosis [ 13 ], hepatoprotective [ 14 ], antiviral and immunomodulatory [ 15 ] activities.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the protein-enriched fraction of Musca domestica larvae could promote the phagocytic function of macrophages, 2,4-dinitrofluorobenzene-induced delayed type hypersensitivity reaction, proliferation of lymphocytes, and natural killer cell activity in naïve mice [ 15 ]. In our previou works, the peptide fraction from Musca domestica larvae (MDPF) was found to improve both specific and non-specific cellular and humoral immune response in tumor-bearing mice, and its antitumor activity might be achieved by switching-on of Th1-based protective cell-mediated immunity [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The DPPH radical scavenging effect of the protein extracts from the Cherry Valley ducks was examined according to the method of Ai, Wang, Zhang, Zhang, and Lei (). Briefly, a 5.0 mL solution of protein extracts at different concentrations (0.0625, 0.125, 0.25, 0.5, 1.0, and 2.0 mg/mL) were added into 5.0 mL of 60 μM DPPH solution and, then, the reaction mixture was shaken well and incubated for 30 min without light.…”
Section: Methodsmentioning
confidence: 99%
“…2.12 | Natural killer (NK) cells activity assay NK cell activity was measured according to the method of Ai et al (2013) and Zhao et al (2017). The splenic lymphocytes were prepared as above and suspended in complete RPMI-1640 medium (1.0 3 10 6 / mL).…”
Section: Splenocyte Proliferation Assaymentioning
confidence: 99%